2020
DOI: 10.3762/bjnano.11.163
|View full text |Cite
|
Sign up to set email alerts
|

Self-standing heterostructured NiCx-NiFe-NC/biochar as a highly efficient cathode for lithium–oxygen batteries

Abstract: Lithium–oxygen batteries have attracted research attention due to their low cost and high theoretical capacity. Developing inexpensive and highly efficient cathode materials without using noble metal-based catalysts is highly desirable for practical applications in lithium–oxygen batteries. Herein, a heterostructure of NiFe and NiC x inside of N-doped carbon (NiC x -NiFe-NC) derived from bimetallic Prussian blue supported on biochar was developed as a novel self-standing cathode for lithium–oxygen batteries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…3d, the N 1s peak of 398.5 eV belongs to the CN bond of Ni–Co PBA. 44 As for the metallic elements of Ni–Co PBA, the typical peaks of Co 2p are observed at 782.3 eV for 2p 3/2 and 797.2 eV for 2p 1/2 (Fig. 3e), and Ni 2p shows the typical peaks of 857.3 eV for 2p 3/2 , 875.0 eV for 2p 1/2 and two satellite peaks (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…3d, the N 1s peak of 398.5 eV belongs to the CN bond of Ni–Co PBA. 44 As for the metallic elements of Ni–Co PBA, the typical peaks of Co 2p are observed at 782.3 eV for 2p 3/2 and 797.2 eV for 2p 1/2 (Fig. 3e), and Ni 2p shows the typical peaks of 857.3 eV for 2p 3/2 , 875.0 eV for 2p 1/2 and two satellite peaks (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…2c and revealed that the major surface functional groups were C–C, CC, and CO around 284.7, 285.2, and 286.5 eV, respectively. 17,75,76 The O1's distinct peaks are depicted in Fig. 2d, which demonstrated that its main functional groups were O–C, OC, and O–H at 531.5, 532.9, and 534 eV, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…2d, which demonstrated that its main functional groups were O–C, OC, and O–H at 531.5, 532.9, and 534 eV, respectively. 17,76…”
Section: Resultsmentioning
confidence: 99%
“…The BE of 860.2 eV is characteristic of related satellite peaks. The slightly lower BE of 854.5 eV is assigned to partially reduced nickel species with a positive charge δ+ (Ni δ+ ), indicative of the presence of a nickel carbide phase [30][31][32][33]. As the synthesis time increases, the ratio of this peak to the 2+ peak gradually increases, indicating that the ratio of nickel carbide in the powder increases.…”
Section: Resultsmentioning
confidence: 99%